Portrait sociolinguistique de travailleurs étrangers temporaires agricoles au Québec : entre barrières et besoins - Collin, Simon; Calonne, Olivier (Canadian Journal of Applied Linguistics, 2021)
An influx of temporary migrant workers represents a growing trend in the contemporary migration landscape. While many studies note that temporary migrant workers are facing linguistic challenges that are impacting their migration experience, few investigations have examined their sociolinguistic reality. This research aims to better understand the sociolinguistic experience of temporary migrant workers working on a farm in Québec. Twenty-four temporary migrant workers completed a questionnaire and participated in focus groups designed to probe their sociolinguistic experiences. The results demonstrate that while the participants’ proficiency in written Spanish, English, and French is limited, the host society affords them few opportunities to communicate in any language other than Spanish. Overall, the participants are facing sociolinguistic barriers that prevent them from acquiring French. Implications for designing French language courses to address migrant workers’ sociolinguistic needs are discussed.